Data representation and serialization - Dennison, Justin; Spurgin, Aubri (Packt Publishing Ltd., 2024)
Embark on a journey to master essential data formats crucial for any data-driven professional. The course begins with a deep dive into CSV files, teaching you how to explore and manipulate them using Python's csv module and the powerful pandas and tablib packages. You'll learn the ins and outs of CSV files, ensuring you can handle them with ease and efficiency. Moving forward, the focus shifts to JSON files, where you'll understand their structure and how to work with them using the json module. The course further explores advanced JSON handling with pandas and introduces you to additional packages like simplejson, ujson, and tablib. This segment ensures you are well-equipped to manage JSON data in various contexts. The course also covers YAML, XML, and HTML files, providing a comprehensive understanding of each format. You'll explore YAML files and use the PyYAML and tablib packages for effective manipulation. The XML and HTML sections delve into their respective file structures, and you'll learn to use the xml, lxml, xmltodict, and BeautifulSoup packages. By the end of this course, you'll be proficient in handling these diverse data formats, significantly boosting your data processing capabilities.
Online resource; title from title details screen (O'Reilly, viewed June 3, 2024)
Keywords: Data structures (Computer science); Programming languages (Electronic computers); Structures de données (Informatique); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet